Baseline Susceptibility of Field Populations of Helicoverpa armigera to Bacillus thuringiensis Vip3Aa Toxin and Lack of Cross-Resistance between Vip3Aa and Cry Toxins - Wei, Yiyun; Wu, Shuwen; Yang, Yihua; Wu, Yidong (Toxins, 2017)
The cotton bollworm Helicoverpa armigera (Hübner) is one of the most damaging cotton pests worldwide. In China, control of this pest has been dependent on transgenic cotton producing a single Bacillus thuringiensis (Bt) protein Cry1Ac since 1997. A small, but significant, increase in H. armigera resistance to Cry1Ac was detected in field populations from Northern China. Since Vip3Aa has a different structure and mode of action than Cry proteins, Bt cotton pyramids containing Vip3Aa are considered as ideal successors of Cry1Ac cotton in China. In this study, baseline susceptibility of H. armigera to Vip3Aa was evaluated in geographic field populations collected in 2014 from major cotton-producing areas of China. The LC50 values of 12 field populations ranged from 0.053 to 1.311 μg/cm2, representing a 25-fold range of natural variation among populations. It is also demonstrated that four laboratory strains of H. armigera with high levels of resistance to Cry1Ac or Cry2Ab have no cross-resistance to Vip3Aa protein. The baseline susceptibility data established here will serve as a comparative reference for detection of field-evolved resistance to Vip3Aa in H. armigera after future deployment of Bt cotton pyramids in China.